Entry-Level Civil Service Leadership Development Programs : Survey of Selected International Experience - Roseth, Benjamin (World Bank, Washington, DC, 2016)
This note presents an overview of several entry-level civil service leadership development programs (ELDP), defined here as a government program – separate from mainstream civil service recruitment and development mechanisms – that seeks to recruit young professionals, select the best candidates based on merit, develop their skills to meet the business needs of government ministries and programs while preparing them for leadership in the civil service. It draws on experiences from the Unites States, the United Kingdom, Singapore and Liberia. All of the programs analyzed cover the national or federal level of government. The remainder of the note is organized into five sections: (i) Background, which places ELDPs in the broader context of civil service reform; (ii) Advent of ELDPs, which describes the challenges ELDPs were designed to address; (iii) Analysis of Programs, which describes the general characteristics typical to ELDPs; (iv) Country cases, which highlights salient characteristics of each of the four ELDPs analyzed; and (v) Initial thoughts on introducing such programs.